Whereabouts and Secrets: A Person-Centered Approach to Emerging Adults' Routine and Self-Disclosure to Parents. Issue 2 (April 2021) - Son, Daye; Padilla-Walker, Laura M.
The current study examined heterogeneity in emerging adult children's routine and self-disclosure to parents using mixture modeling and explored predictors and outcomes associated with the patterns of disclosure. Participants consisted of 449 emerging adults (49% male, 68% European American, 65% college students, 33% single-parent families) who completed questionnaires every year across three waves ( M age at Time 1 = 18.4 years). Latent profile analyses suggested that large groups of emerging adults reported moderate levels of routine disclosure and low levels of self-disclosure to both mothers (79%) and fathers (36%), while other groups (20%) reported high levels of routine and self-disclosure to both parents. Profile membership was associated with predictors (parental autonomy granting, self-disclosure to friend, gender, family structure, college attendance) at Time 1 and outcomes (delinquency, depression, and prosocial behavior) at Time 3. Implications regarding the continued parent–child relationship and disclosure to parents in the third decade of life are discussed.